Determinants of litter decomposition rates in a tropical forest: functional traits, phylogeny and ecological succession. Issue 8 (15th February 2017) - Szefer, Piotr; Carmona, Carlos P.; Chmel, Kryštof; Konečná, Marie; Libra, Martin; Molem, Kenneth; Novotný, Vojtěch; Segar, Simon T.; Švamberková, Eva; Topliceanu, Theodor‐Sebastian; Lepš, Jan
Abstract : Plant litter decomposition is one of the most important processes in terrestrial ecosystems, as it is a key factor in nutrient cycling. Decomposition rates depend on environmental factors, but also plant traits, as these determine the character of detritus. We measured litter decomposition rate for 57 common tree species displaying a variety of functional traits within four sites in primary and four sites in secondary tropical forest in Madang Province, Papua New Guinea. The phylogenetic relationships between these trees were also estimated using molecular data. The leaves collected from different tree species were dried for two days, placed into detritus bags and exposed to ambient conditions for two months. Nitrogen, carbon and ash content were assessed as quantitative traits and used together with a phylogenetic variance– covariance matrix as predictors of decomposition rate. The analysis of the tree species composition from 96 quadrats located along a successional gradient of swidden agriculture enabled us to determine successional preferences for individual species. Nitrogen content was the only functional trait measured to be significantly positively correlated with decomposition rate. Controlling for plant phylogeny did not influence our conclusions, but including phylogeny demonstrated that the mainly early successional family Euphorbiaceae is characterized by a particularly high decomposition rate. The acquisitive traits (high nitrogen content and low wood density) correlated with rapid decomposition were characteristic for early successional species. Decomposition rate thus decreased from early successional to primary forest species. However, the decomposition of leaves from the same species was significantly faster in primary than in secondary forest stands, very probably because the high humidity of primary forest environments keeps the decomposing material wetter.